Endurance Is Improved in Female Rats After Living High-Training High Despite Alterations in Skeletal Muscle - Malgoyre, Alexandra; Prola, Alexandre; Meunier, Adelie; Chapot, Rachel; Serrurier, Bernard; Koulmann, Nathalie; Bigard, Xavier; Sanchez, Hervé (Frontiers in Sports and Active Living, 2021)
Altitude camps are used during the preparation of endurance athletes to improve performance based on the stimulation of erythropoiesis by living at high altitude. In addition to such whole-body adaptations, studies have suggested that high-altitude training increases mitochondrial mass, but this has been challenged by later studies. Here, we hypothesized that living and training at high altitude (LHTH) improves mitochondrial efficiency and/or substrate utilization. Female rats were exposed and trained in hypoxia (simulated 3,200 m) for 5 weeks (LHTH) and compared to sedentary rats living in hypoxia (LH) or normoxia (LL) or those that trained in normoxia (LLTL). Maximal aerobic velocity (MAV) improved with training, independently of hypoxia, whereas the time to exhaustion, performed at 65% of MAV, increased both with training (P = 0.009) and hypoxia (P = 0.015), with an additive effect of the two conditions. The distance run was 7.98 ± 0.57 km in LHTH vs. 6.94 ± 0.51 in LLTL (+15%, ns). The hematocrit increased >20% with hypoxia (P < 0.001). The increases in mitochondrial mass and maximal oxidative capacity with endurance training were blunted by combination with hypoxia (−30% for citrate synthase, P < 0.01, and −23% for Vmax glut−succ, P < 0.001 between LHTH and LLTL). A similar reduction between the LHTH and LLTL groups was found for maximal respiration with pyruvate (−29%, P < 0.001), for acceptor-control ratio (−36%, hypoxia effect, P < 0.001), and for creatine kinase efficiency (−48%, P < 0.01). 3-hydroxyl acyl coenzyme A dehydrogenase was not altered by hypoxia, whereas maximal respiration with Palmitoyl-CoA specifically decreased. Overall, our results show that mitochondrial adaptations are not involved in the improvement of submaximal aerobic performance after LHTH, suggesting that the benefits of altitude camps in females relies essentially on other factors, such as the transitory elevation of hematocrit, and should be planned a few weeks before competition and not several months.